Peningkatan Hasil Belajar IPS Materi Jenis-jenis Pekerjaan Melalui Model Pembelajaran Make A-Match pada Siswa Kelas III SD Muhammadiyah 2 Samarinda - Nurul Hikmah (Teacher Training and Education Faculty, Widya Gama Mahakam Samarinda University, 2018)
This study aims to determine the improvement of Social Studies Learning Outcomes of the Types of Work through Make A-Match Learning Model in Class III Students of SD Muhammadiyah 2 Samarinda. This type of research is Classroom Action Research (CAR), which was carried out at SD Muhammadiyah Samarinda precisely in class III, totaling 36 students. Data collection techniques used in this study are observation sheets of teacher and student activities during the learning process, written tests, documentation.This research was carried out in two cycles and each cycle consisted of two meetings, each cycle consisting of four stages, namely the planning, implementation, observation and reflection stages. Based on observational data obtained in each cycle, it can be seen that student learning outcomes improve well. The results show that through the Make A-Match learning model can improve student learning outcomes. Increased student learning outcomes from prasiklus by 11.1% with an average value of 55.3 then increased in the first cycle by 25% with an average value of 65. Then in the second cycle experienced an increase of 94.4% with the average value of students 80.4. By applying make a-match learning model can increase student activity in the teaching and learning process, this can be seen by an increase in each cycle. The percentage in pre-cycle is 55.5%. Furthermore, the first cycle is 74.3%, the percentage in the second cycle is 87.45%.The conclusion in this study using the Make A-Match learning model can improve learning outcomes and activities of third grade students of SD Muhammadiyah 2 Samarinda.